PERTUMBUHAN DAN HASIL TANAMAN KANGKUNG DARAT (Ipomoea reptans Poir) AKIBAT PEMBERIAN PUPUK KASCING - I Komang Juniada Alit Wirawan; I Made Suryana; I Made Sukerta (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2021)
This research title is "Growth and Yield of ground water spinach plants (Ipomoea reptans Poir) Due to Treatment of Kascing fertilizer was accepted on Tukad Oos street, Renon, south Denpasar City, Bali from 23 October until 2 December 2019. This research has been conducted to determine the effect and the best dose of Kascing fertilizer on the growth and yield of ground water spinach plants. This research used a randomized block design (RAK) with 6 treatments and 4 replications until obtained 24 treatments total. The result showed that the application of Kascing fertilizer at a dose of 15 tons ha-1 or equivalent to 75 g in 10 kg of soil was able to provide the best growth and results, with the highest fresh weight result of plants above the soil at P5 treatment that is 131.04 g and decreased significantly in P0 treatment that is 103.60 g